Model Pengambilan Keputusan Calon Penerima Bantuan Usaha Mikro Bank Lampung Dengan Metode Weighted Product Di Pringsewu - Muhammad Junaidi; Fiqih Satria; Garaika Garaika (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2020)
Weighted Product is one of the methods used in solving the problem of FADM (Fuzzy Multi Atribute Decision Making). Weighted Product requires a normalization process because it multiplies the assessment results of each attribute, the multiplication results have not meaningful if not yet compared with the standard value. The weights for attributes serve as positive ranks in the multiplication process, while the cost weight serves as a negative rank. The steps taken in the process of Weighted Product method is by using multiplication for each criteria match rating and rating the each criterion with the weight of the criteria. This method is used to find the best alternative from so many alternatives with the best weights. From the completion of this thesis, the authors conducted a study in how to select candidates for micro business assistance bank Lampung